Forces of nature stories from the Brower Youth Awards - Brower Youth Awards; Earth Island Institute; Rikshaw Films; Video Project (California : Video Project, 2009)
"Forces of Nature profiles the inspirational work of individuals recognized with North America's top environmental prize for youth, the Brower Youth Award. Their stories illuminate our world's most pressing environmental challenges, including climate change, deforestation, air and water pollution, destructive mining, and much more, all through the lens of youth ages 13-22, who are forging solutions and building grassroots movements for change"
Keywords: Energy consumption; Environmental protection -- Awards; Social change; Social history